2013
DOI: 10.1093/ageing/afs200
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on the management of pain in older people

Abstract: This guidance document reviews the epidemiology and management of pain in older people via a literature review of published research. The aim of this document is to inform health professionals in any care setting who work with older adults on best practice for the management of pain and to identify where there are gaps in the evidence that require further research. The assessment of pain in older people has not been covered within this guidance and can be found in a separate document (http://www.britishpainsoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
259
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(279 citation statements)
references
References 250 publications
9
259
0
11
Order By: Relevance
“…Multi-modal approaches that include alternative non-nutraceutical treatment are recommended to reduce pain and, therefore, should be part of standard pain management. 11 The purpose of this research was thus to describe alternative nonpharmaceutical non-nutraceutical chronic pain self-management strategies used by patients hospitalized for HF.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-modal approaches that include alternative non-nutraceutical treatment are recommended to reduce pain and, therefore, should be part of standard pain management. 11 The purpose of this research was thus to describe alternative nonpharmaceutical non-nutraceutical chronic pain self-management strategies used by patients hospitalized for HF.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent study investigating the effectiveness of SMT and exercise interventions among seniors (aged 65 and above) with chronic neck pain [43] information on AE was systematically collected [44]. The AE identified were primarily musculoskeletal or pain related and non-serious and this is consistent with current evidence on AE following SMT and exercise [15,19,24,45] suggesting that these interventions have a lower risk of harm relative to other commonly used pharmacological interventions for neck pain [42]. …”
Section: Discussionmentioning
confidence: 68%
“…The United Nations predict that the proportion of people aged 60 years and over will triple over the next 40 years and will account for more than 20% of the world’s population by year 2050 [40]. Manifestations of musculoskeletal disorders increase with age [41] making interventions with documented effect and a favourable risk profile desirable [42]. In one recent study investigating the effectiveness of SMT and exercise interventions among seniors (aged 65 and above) with chronic neck pain [43] information on AE was systematically collected [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pain management program, which includes physical activity, has been shown to have health benefits and improve pain management among older adults [8], studies have found educational interventions to be effective among older adults only over the short term [9]. People who participated in these interventional programs often fell back into their old habits of inactivity after completing the program [10].…”
Section: Introductionmentioning
confidence: 99%